Reconciling Svalbard Glacier Mass Balance - Schuler, Thomas V.; Kohler, Jack; Elagina, Nelly; Hagen, Jon Ove M.; Hodson, Andrew J.; Jania, Jacek A.; Kääb, Andreas M.; Luks, Bartłomiej; Małecki, Jakub; Moholdt, Geir; Pohjola, Veijo A.; Sobota, Ireneusz; et al. (Frontiers in Earth Science, 2020)
Since the first estimates of Svalbard-wide glacier mass balance were made in the early 2000s, there has been great progress in remote sensing and modeling of mass balance, existing field records have been extended, field records at new locations have been added, and there has been considerable environmental change. There is a wide spread in the available estimates of both total mass balance and surface or climatic mass balance, but there is overall agreement that the glaciers on Svalbard have been losing mass since the 1960s, with a tendency toward more negative mass balance since 2000. We define criteria to select data that are representative and of high credibility; this subset shows a more coherent evolution and reduced spread. In addition, we combine individual field mass balance records collected by different groups into a single dataset that samples glaciers across Svalbard and a range of different size classes. We find a close relationship between measured specific surface mass balance and size of the glacier, in such a way that smaller glaciers experience more negative surface mass balances. A qualitatively similar relationship between the accumulation area ratio and glacier area is found for all glaciers in the Svalbard, suggesting that the relation derived from glaciological records is not only an artifact caused by the limited number of samples (n = 12). We apply this relation to upscale measured surface mass balance for a new estimate for all glaciers of Svalbard. Our reconciled estimates are −7 ± 4 Gt a–1 (2000–2019) for the climatic mass balance, and −8 ± 6 Gt a–1 for the total mass balance. The difference between the two represents the sum of frontal ablation and the combined uncertainty, which together amount to ca. −2 ± 7 Gt a–1. While this is consistent with a previous estimate of Svalbard-wide frontal ablation, the uncertainties are large. Furthermore, several large and long-lasting surges have had considerable and multi-year impact on the total mass balance, and in particular on calving rates, emphasizing the need for better-resolved and more frequently updated estimates of frontal ablation.